Adsorption behavior of tetraethylenepentamine-functionalized Si-MCM-41 for CO2 adsorption - Ahmed, S. (Institution of Chemical Engineers, 2017)
Carbon dioxide (CO2) mitigation is of prime importance due to its prodigious release into the atmosphere from power plants and other industrial sources which directly influence the climate change. Adsorption process is considered as an attractive process for CO2 separation and purification due to low energy requirement, cost-effective and ease in applicability over wide range of operating conditions. In this work, mesoporous Si-MCM-41 was functionalized with different loadings of tetraethylenepentamine (TEPA) to study its performance for CO2 adsorption using gravimetric technique. The adsorption data shows that incorporation of TEPA into Si-MCM-41 promotes CO2 adsorption and the adsorption capacity increases with increasing loading of TEPA from 10 to 50 wt.. The 50 wt. TEPA-functionalized Si-MCM-41 shows the CO2 adsorption capacity of 54.65 mg/g at 25 °C and 1 bar. Further studies shows that the adsorption capacity of 50 wt. TEPA-Si-MCM-41 increases with increasing temperature from 25 to 75 °C with the highest CO2 adsorption capacity of 70.41 mg/g at 75 °C and 1 bar. Infrared spectroscopy was used to study the interaction mechanism of CO2 with amino groups using the 50 wt. TEPA-Si-MCM-41. FTIR spectra of CO2-saturated 50 wt. TEPA-Si-MCM-41 samples showed peaks related to carbamates formation which is the evidence of chemisorption process. © 2017 Institution of Chemical Engineers